Method for comprehensively recovering iron and sulfur from sulfur-containing iron slag
Through the treatment of sulfur -containing iron residue and band roasting, the depth separation and difficulty of sulfur and iron elements are solved, and efficient resource recovery and environmental protection are achieved.
Patent Information
- Application Number
- CN202411453294.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to deeply separate sulfur and iron elements in sulphur-containing iron slag, and recycling is difficult, resulting in waste of resources and environmental pollution.
By briquetting the sulfur-containing iron slag and combining it with a belt roaster for heat treatment, efficient separation of sulfur and iron elements is achieved. This method includes steps such as drying, crushing, classification and briquetting to ensure the appropriate moisture and particle size distribution of the raw materials, thereby improving the continuity and efficiency of the roasting process.
It achieves efficient separation of sulfur and iron elements in sulfur-containing iron slag, obtains iron ore agglomeration or iron-making raw materials that can be used for external sales, and centralizes the emission of sulfur dioxide to obtain high-concentration sulfur dioxide flue gas, which is beneficial to acid production. .
Smart Images

Figure CN119351726A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for treating sulfur-containing iron slag, in particular to a method for comprehensively recovering iron and sulfur from sulfur-containing iron slag, and belongs to the technical field of comprehensive utilization of metallurgy and industrial solid waste. Background Art
[0002] With the rapid development of global industry, the scale and production capacity of non-ferrous smelting and chemical industry have grown rapidly, which also brings severe challenges to environmental protection. Sulfur-containing iron slag is one of the common main waste slags in non-ferrous smelting and chemical industry, such as high-pressure acid leaching slag of laterite nickel ore, atmospheric acid leaching slag of laterite nickel ore, high-pressure-normal pressure combined acid leaching slag of laterite nickel ore, sulfuric acid slag, etc. The slag volume is large and resource utilization is difficult. It is often treated by direct stockpiling, which not only causes serious waste of land, but also easily causes ecological and environmental safety hazards such as slag mudslides, harmful ions and heavy metal ion pollution. Sulfur-containing iron slag contains rich sulfur and iron elements. If it can be recycled as a resource, it can protect the environment while effectively reducing dependence on primary mineral resources.
[0003] However, in the actual production process of non-ferrous smelting and chemical industries, in order to meet the process efficiency and recovery rate, whether it is a pyrometallurgical or hydrometallurgical process, it is often necessary to grind the raw materials into extremely fine materials. Most of the sulfur-containing iron slag is directly formed by the original material, while the sulfur-containing iron slag of some hydrometallurgical processes is produced by the precipitation and impurity removal stage. These directly determine the small particle size of the final sulfur-containing iron slag, resulting in it being difficult to deeply separate sulfur and iron in the physical sorting stage even after further processing, such as magnetization roasting, direct reduction and other low-temperature reduction roasting and separation processes. In addition, although this type of process can achieve iron enrichment, its recovery rate is low, and the sulfur-containing compounds in the form of calcium sulfate in the slag are extremely sensitive to temperature. It is impossible to completely remove this type of sulfur at low temperatures. The sulfur eventually flows to the recovery of iron concentrate / iron, tailings, and flue gas, and cannot be recycled.
[0004] In terms of high-temperature oxidation roasting, the "chain-return-loop" process and belt machine process for iron ore pellets are expected to make it possible to deeply separate sulfur and iron elements in sulfur-containing iron slag. In view of process requirements, the raw materials must be disc-pelletized before roasting. However, the above-mentioned sulfur-containing iron slag is difficult to pelletize due to its small particle size, many voids, large specific surface area, strong water absorption capacity, high water holding capacity, and subsequent drying process. There is a high risk of explosion and pulverization. The sulfur-containing iron slag pellets also have a high loss on burnout rate and poor density during the roasting process. If the "chain-return-loop" process is adopted, the slag roasting balls are easily broken and pulverized due to the strong mechanical impact and wear of the pellets during the rotary motion of the rotary kiln, which makes the process difficult to run smoothly. In addition, after the pellets enter the rotary kiln, the temperature gradually rises and enters the high-temperature roasting process. The degree of concentrated removal of sulfur elements is poor, and the flue gas cannot be collected in sections. Finally, sulfur exists in the flue gas in the form of low-concentration (<1%) sulfur dioxide. Due to the economic problems of desulfurization, this type of flue gas basically adopts flue gas desulfurization (FGD) technology, and the desulfurization by-products are discarded, making it difficult to achieve resource recycling.
[0005] Therefore, developing a method for realizing large-scale resource utilization of sulfur-containing iron slag has great significance and impact on the recycling of sulfur and iron resources in sulfur-containing iron slag and environmental protection. Summary of the invention
[0006] In view of the technical problems that the existing process is difficult to deeply separate the sulfur and iron elements in sulfur-containing iron slag, and is also difficult to recycle, the purpose of the present invention is to provide a method for comprehensively recovering iron and sulfur from sulfur-containing iron slag. The method can effectively avoid the breakage and pulverization of agglomerates during the roasting process by briquetting the sulfur-containing iron slag and combining it with a belt roasting machine for heat treatment, which is beneficial to the continuous completion of the process, and especially realizes the efficient separation of iron and sulfur elements. Not only can the iron ore agglomerates or ironmaking raw materials that meet the requirements be obtained, but also the sulfur dioxide can be discharged in a centralized manner to obtain sulfur dioxide flue gas with a higher concentration, which is beneficial to acid production.
[0007] In order to achieve the above technical objectives, the present invention provides a method for comprehensively recovering iron and sulfur from sulfur-containing iron slag, the method comprising the following steps:
[0008] 1) drying, crushing, grading and briquetting the sulfur-containing iron slag to obtain briquettes;
[0009] 2) placing the agglomerates on a belt roasting machine trolley, and sequentially performing forced air drying, exhaust air drying, roasting, soaking and cooling to obtain roasted agglomerates; wherein, the flue gas with a sulfur dioxide volume concentration greater than 1.0% generated during the roasting process is separately collected for preparing sulfuric acid, and the roasted agglomerates are used as raw materials for iron ore agglomeration or ironmaking.
[0010] In terms of raw material pretreatment, the present invention aims at the problems of high drying difficulty, easy agglomeration, poor moisture uniformity, etc. caused by the high water content of sulfur-containing iron slag, and adopts drying (rotary dryer), crushing (roller crusher), grading (high-frequency screen) and other operations in sequence, so as to obtain raw materials with suitable moisture content and particle size, which can better meet the subsequent pressing and molding process. In addition, with regard to the crushing operation process, not only can the sulfur-containing compounds mixed in the pyrometallurgical sulfur-containing iron slag, which are wrapped in the gangue or ore, be dissociated, but also the sulfur-containing calcium sulfate phase with good crystallinity, large particle size, high decomposition temperature and long time in the wet leaching sulfur-containing iron slag can be further refined and activated, which is beneficial to promote the rapid oxidation or decomposition of the sulfur-containing phase in the subsequent high-temperature treatment of the slag, and realize the deep removal of sulfur in the slag.
[0011] In terms of agglomeration and roasting, the present invention adopts a briquetting process based on the common physical properties of sulfur-containing iron slag, such as fine particle size, high porosity, large specific surface area, and strong water absorption capacity. During the briquetting process, on the one hand, the sulfur-containing iron slag particles are easy to hook and wedge due to the high surface roughness, resulting in mechanical meshing between particles. On the other hand, the particles of the sulfur-containing iron slag have a large contact surface area and enhanced molecular bonding. The two aspects work together to easily achieve the preparation of high-strength raw material agglomerates under low moisture conditions. The agglomerates adopt a belt roasting machine roasting process during the heat treatment process. The belt roasting machine has the advantages of easy and precise temperature control and segmented collection of flue gas. On the one hand, by abolishing the traditional preheating interval and constructing a rapid high-temperature roasting mode in which the pellet material directly enters the high-temperature roasting zone after drying, it is conducive to the rapid and concentrated removal of various sulfur-containing phases to achieve the effect of sulfur dioxide enrichment; on the other hand, the characteristic of segmented collection of flue gas is used to obtain the minimum sulfur dioxide flue gas concentration that meets the economic efficiency of the acid production process.
[0012] As a preferred scheme, the temperature of the blast drying is 150-450°C, the time is 2-6 min, and the wind speed is 1.3-1.7 m / s; the temperature of the exhaust drying is 200-500°C, the time is 3-8 min, and the wind speed is 1.3-1.7 m / s; the temperature of the roasting is 1000-1300°C, the time is 20-120 min, and the wind speed is 1.8-2.6 m / s; the temperature of the soaking is 800-1200°C, the time is 2-6 min, and the wind speed is 1.4-2.2 m / s; the cooling is blast cooling, the time is 15-35 min, the wind speed is 1.4-2.2 m / s, and the temperature of the cooled roasted ball material is <150°C. Taking advantage of the fact that the temperature of the belt roaster is easy to accurately control, the agglomerates are directly put into high-temperature roasting after drying, and different types of sulfur phases in the sulfur-containing iron slag are concentratedly removed and discharged in the early stage of high-temperature roasting, creating necessary conditions for the subsequent recycling of sulfur resources. The present invention adopts a drying method combining blast drying and exhaust drying to prevent the problem of structural damage of the lower material layer due to excessive moisture condensation under unidirectional airflow drying.
[0013] As a preferred solution, the main chemical components and mass contents of the sulfur-containing iron slag are: TFe25-68%, SiO2<40%, Al2O3<18%, CaO<20%, MgO<18%, S0.7-12%. After high-temperature roasting, the iron grade of the sulfur-containing iron slag will be further improved, but when the total iron content is lower than 25%, the iron grade of the final roasting product is low, which is not conducive to the economic recycling of iron elements in downstream industries. The inherent chemical substances such as SiO2, Al2O3, CaO, MgO in the sulfur-containing iron slag are conducive to compression molding, and are also conducive to the consolidation of agglomerates during high-temperature roasting. However, if the proportion of one or more of these components is too high, it may be unfavorable to the formation of compounds or solid solutions that play a consolidating role during the roasting process, and may cause excessive liquid phase generation, resulting in poor permeability of the material layer and low processing efficiency. When the sulfur content in the sulfur-containing iron slag is lower than 0.7%, the sulfur dioxide concentration in the flue gas during the roasting process will be too low. Except for the use of absorption regeneration and sulfur supplementation, it is difficult to meet the acid production requirements and the overall economic efficiency is poor. If the sulfur content is too high, it will be detrimental to the corrosion resistance and anti-aging properties of the belt roasting equipment.
[0014] As a preferred solution, the sulfur-containing iron slag, after drying, crushing and grading, has a moisture content of 2% to 15%, and the mass proportion of particles below 100 μm is greater than 80%. The moisture content in the sulfur-containing iron slag has a great influence on the performance of the agglomerate. If its moisture content is too low, it is difficult to press and form and cannot maintain sufficient strength. If its moisture content is too high, the bursting temperature is reduced, and it is easy to produce pulverization, which is not conducive to the smooth process, and the heat loss taken away by the drying process is large. The appropriate content of fine-grained materials helps to form a stronger binding force between particles, thereby improving the strength and stability of the pressed agglomerates.
[0015] As a preferred solution, the sulfur-containing iron slag includes at least one of laterite nickel ore high pressure acid leaching slag, laterite nickel ore normal pressure acid leaching slag, laterite nickel ore high pressure-normal pressure combined acid leaching slag, and sulfuric acid slag.
[0016] As a preferred solution, the linear pressure ratio of the briquetting machine during the briquetting process is 1 to 15 t / cm. During the briquetting process, the sulfur-containing iron slag must be formed and able to meet the subsequent belt machine heat treatment process. The molding pressure must be appropriate. If the pressure is too low, the formed briquette of the sulfur-containing iron slag will have insufficient compression and impact strength, and will easily break during the process, affecting the smooth progress of the belt machine heat treatment process; if the pressure is too high, the compaction density of the formed briquette of the sulfur-containing iron slag will be high, the kinetic conditions for sulfur removal from the briquette will be poor, the roasting time will be long, and the energy consumption will be high. The linear pressure ratio during the briquetting process is further preferably 1 to 5 t / cm.
[0017] As a preferred solution, the equivalent volume diameter of the agglomerate is 5 to 23 mm. The particle size of the agglomerate should not be less than 5 mm. If it is lower than this particle size, the air permeability of the material layer will be poor, which is not conducive to the heat transfer efficiency in the material layer and may cause uneven temperature distribution of the material layer. At the same time, the particle size of the agglomerate should not exceed 23 mm. If it exceeds this particle size, it is easy to cause incomplete internal oxidation and poor agglomerate strength. At the same time, if the particle size of the agglomerate is too small or too large, it will lead to low heat utilization efficiency during roasting and substandard removal of sulfur in the agglomerate.
[0018] As a preferred solution, the shape of the agglomerate includes at least one of a cube, a cuboid, a cylinder, a sphere, an ellipsoid and an irregular body. The sulfur-containing iron slag particles themselves have a small particle size. If they are not granulated, the subsequent roasting process cannot be implemented. The shape of the agglomerate mainly affects its packing density. If the packing density is too high, it will lead to poor permeability of the material layer, which is not conducive to high-temperature removal of the sulfur-containing phase, and the heat utilization rate is low, resulting in poor desulfurization effect.
[0019] As a preferred solution, the thickness of the agglomerates on the belt roasting machine trolley is 50 to 450 mm. The thickness of the agglomerates affects the roasting effect and energy consumption. If the material layer is too thin, although the roasting effect is good, the heat utilization efficiency is low and the processing capacity is limited. If the material layer is too thick, due to the problem of air flow resistance and the lower heat conduction efficiency, the temperature distribution of the upper and lower material layers is uneven, and the sulfur content in the agglomerates in the lower part of the material layer is not removed up to the standard.
[0020] As a preferred solution, the calcination temperature is 1000-1300° C. If the calcination temperature is too low, the sulfur-containing phase in the agglomerate cannot be completely decomposed, while if the temperature is too high, the agglomerate will melt and generate a liquid phase, causing the process to fail.
[0021] As a preferred solution, the flue gas in the first 1 / 25 to 3 / 5 length interval of the roasting interval is separately collected during the roasting process for the preparation of sulfuric acid. Based on the sulfur grade of the sulfur-containing iron slag being higher than 0.7%, sulfur dioxide is concentratedly discharged in the initial stage of the belt roasting machine and the flue gas is collected in sections, so that the average concentration of sulfur dioxide in the flue gas can be guaranteed to be greater than 1.0%. The sulfur dioxide concentration of 1% is the minimum limit for the process of preparing sulfuric acid by self-heating balance. Above this concentration, the conventional dry contact acid production process or wet acid production process can be adopted according to actual conditions and needs. No measures such as sulfur supplementation, heat supplementation, and precipitation are required to ensure the thermal balance and water balance of the acid production system, with high heat utilization efficiency and low investment and operating costs. When the length interval is less than 1 / 25, although the sulfur dioxide concentration in the collected flue gas is high, the sulfur dioxide loss is large. When the length interval is greater than 3 / 5, although the sulfur dioxide recovery rate is high, the sulfur dioxide concentration in the flue gas is too low, which is not conducive to the subsequent acid production process. Therefore, in a further preferred embodiment, during the roasting process, the flue gas within the first 1 / 10 to 3 / 10 length of the roasting interval is separately collected for preparing sulfuric acid.
[0022] The sulfur content in the roasted agglomerates of the present invention is less than 0.2%. If the sulfur content in the agglomerates is higher than 0.2%, it will be disadvantageous for the resource recovery and utilization of iron elements in the downstream industries.
[0023] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:
[0024] 1. The present invention aims to solve the problems of high water content of sulfur-containing iron slag, such as difficulty in drying, easy agglomeration, poor uniformity of moisture, etc., and sequentially adopts drying, crushing, grading and other processing operations to obtain materials whose moisture content and particle size meet the requirements of the subsequent pressing and molding process. At the same time, during the crushing process, not only can the sulfur-containing compounds mixed in the pyrometallurgical sulfur-containing iron slag, which are wrapped in the gangue or raw ore, be dissociated, but also the high-decomposition-temperature sulfur-containing phase of calcium sulfate with good crystallinity in the wet leaching sulfur-containing iron slag can be further refined, which promotes the rapid oxidation or decomposition of the sulfur phase in the subsequent high-temperature treatment of the slag, and is conducive to the deep removal of sulfur in the slag.
[0025] 2. The present invention adopts a pressing molding scheme to achieve the characteristics of sulfur-containing iron slag, such as small particle size, high porosity, large specific surface area and high roughness, and stably obtains high-strength pressed agglomerate raw materials at low raw material moisture content. On the one hand, low moisture content can effectively increase the agglomerate bursting temperature, reduce the difficulty of the drying process, and can greatly reduce the heat and energy consumption caused by water evaporation; on the other hand, under high-temperature roasting, high compaction density is conducive to consolidation and chemical reaction between particles, preventing the high porosity caused by the removal of sulfur elements from causing low strength and easy breakage, which is conducive to the smooth process.
[0026] 3. Based on the characteristic of the belt roasting machine that the temperature is easy to accurately control, the present invention constructs a rapid high-temperature roasting mode in which the raw material agglomerates directly enter the high-temperature roasting area after drying, thereby realizing rapid thermal decomposition of various sulfur-containing phases in the dry pellets, achieving the effect of concentrated sulfur removal, and realizing the resource processing of mixed sulfur-containing iron slag with complex sulfur phases and different sulfur phases.
[0027] 4. The present invention can be used for resource utilization of various types of sulfur-containing iron slags with large differences in sulfur and iron content. The method is simple in process, stable and controllable, and highly practical. It can achieve the stable removal of the sulfur content in the sulfur-containing iron slag to below 0.2%, and obtain iron ore agglomeration / ironmaking clean iron-containing materials that can be sold and acid-making flue gas with a stable sulfur dioxide concentration of >1%, while completing the resource recovery and utilization of sulfur and iron elements in the sulfur-containing iron slag. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The present invention is a flow chart of a method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag.
[0029] Figure 2 This is the XRD pattern of the calcined agglomerate in Example 1. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with preferred implementation examples, but is not intended to limit the protection scope of the claims of the present invention.
[0031] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0032] Example 1
[0033] 1) The high-pressure acid leaching residue of laterite nickel ore with a moisture content of 36.87% was dried by a rotary dryer, crushed by a double-roll crusher and sieved with a high-frequency screen to obtain an under-screen briquetting raw material with a moisture content of 10.5% and a particle size of 90% below 100 μm.
[0034] 2) The briquetting raw material is pressed and formed by a high-pressure briquetting machine under the condition of an online pressure ratio of 1.5 t / cm, to obtain a briquetting block with an ellipsoidal shape, an equivalent volume diameter of 14.4 mm, and a compressive strength of >15N (the conventional iron ore pelletizing process can meet the requirement of >10N);
[0035] 3) The pressed blocks are spread on the belt roasting machine trolley to form a 350mm cloth layer, and then subjected to blower drying (temperature 360°C, time 3min, wind speed 1.5m / s), exhaust drying (temperature 380°C, time 5min, wind speed 1.5m / s), roasting (temperature 1250°C, time 40min, wind speed 2.2m / s), heat treatment (temperature 1050°C, time 3min, wind speed 1.8m / s), cooling (time 17min, wind speed 1.8m / s), and subsequently sulfur dioxide fume and roasted blocks are obtained. The sulfur dioxide fume is purified and used to prepare sulfuric acid, and the roasted blocks are used for iron ore agglomeration / ironmaking raw materials for sale. The XRD pattern of the roasted blocks is shown below. Figure 2 As shown, the iron mainly exists in the form of iron oxide rather than in the form of calcium ferrite. However, calcium ferrite has a strong adsorption capacity for sulfur when it melts at low temperature, which is not conducive to the efficient removal of sulfur.
[0036] In this embodiment, the main chemical components in the high pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (27.99%), SiO2 (9.81%), Al2O3 (6.71%), CaO (9.99%), MgO (2.24%), and S (7.60%), wherein sulfur element mainly exists in the form of sulfate. The main chemical components in the calcined agglomerate obtained after heat treatment in step 3) are TFe (39.17%), SiO2 (13.74%), Al2O3 (9.11%), CaO (13.60%), MgO (3.36%), and S (0.033%), which can be used for molten pool smelting to recover iron raw materials. The average concentration of sulfur dioxide in the flue gas of the first 1 / 8 section of the calcination treatment interval along the direction of the trolley is 4.46%, and sulfuric acid can be prepared by conventional dry contact acid production process.
[0037] Example 2
[0038] 1) The high-pressure acid leaching residue of laterite nickel ore with a moisture content of 36.87% was dried by a rotary dryer, crushed by a double-roll crusher and sieved with a high-frequency screen to obtain an under-screen briquetting raw material with a moisture content of 10.5% and a particle size of 90% below 100 μm.
[0039] 2) The briquetting raw material is pressed and formed by a high-pressure briquetting machine under the condition of an online pressing ratio of 1.5 t / cm, to obtain a briquetting block with an ellipsoidal shape, an equivalent volume diameter of 11.5 mm, and a compressive strength of more than 13N;
[0040] 3) The pressed agglomerates are distributed on the belt roasting machine trolley to form a 300 mm distribution layer, and then subjected to blower drying (temperature 320°C, time 2.5 min, wind speed 1.5 m / s), exhaust drying (temperature 335°C, time 4.5 min, wind speed 1.5 m / s), roasting (temperature 1230°C, time 40 min, wind speed 2.2 m / s), heat soaking (temperature 1050°C, time 3 min, wind speed 1.8 m / s), cooling (time 17 min, wind speed 1.8 m / s), and subsequently sulfur dioxide flue gas and roasted agglomerates are obtained. The sulfur dioxide flue gas is purified and used to prepare sulfuric acid, and the roasted agglomerates are used for iron ore agglomeration / ironmaking raw materials for sale.
[0041] In this embodiment, the main chemical components in the high-pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (27.99%), SiO2 (9.81%), Al2O3 (6.71%), CaO (9.99%), MgO (2.24%), and S (7.60%), wherein sulfur element mainly exists in the form of sulfate. The main chemical components in the roasted agglomerates obtained after heat treatment in step 3) are TFe (39.22%), SiO2 (13.77%), Al2O3 (9.08%), CaO (13.63%), MgO (3.33%), and S (0.033%), which can be used for molten pool smelting to recover iron raw materials. The average concentration of sulfur dioxide in the flue gas of the first 1 / 4 section of the roasting treatment area along the direction of the trolley is 1.38%, and sulfuric acid can be prepared by wet acid production process.
[0042] Example 3
[0043] 1) The atmospheric pressure acid leaching residue of laterite nickel ore with a moisture content of 28.23% was dried by a rotary dryer, crushed by a double-roll crusher and sieved with a high-frequency sieve to obtain an under-screen briquetting raw material with a moisture content of 11.2% and a particle size of 100 μm or less accounting for 100%.
[0044] 2) The briquetting raw material is pressed and formed by a high-pressure briquetting machine under the condition of an online pressing ratio of 2.0 t / cm to obtain a briquetting block with an ellipsoidal shape, an equivalent volume diameter of 14.4 mm, and a compressive strength of more than 18N;
[0045] 3) The pressed agglomerates are distributed on the belt roasting machine trolley to form a 370 mm distribution layer, and then subjected to blower drying (temperature 335°C, time 4 min, wind speed 1.5 m / s), exhaust drying (temperature 350°C, time 6 min, wind speed 1.5 m / s), roasting (temperature 1200°C, time 25 min, wind speed 2.2 m / s), heat soaking (temperature 1050°C, time 3 min, wind speed 1.8 m / s), cooling (time 17 min, wind speed 1.8 m / s), and subsequently sulfur dioxide flue gas and roasted agglomerates are obtained. The sulfur dioxide flue gas is purified and used to prepare sulfuric acid, and the roasted agglomerates are used for iron ore agglomeration / ironmaking raw materials for sale.
[0046] In this embodiment, the main chemical components in the atmospheric pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (54.25%), SiO2 (7.07%), Al2O3 (2.51%), CaO (0.45%), MgO (0.28%), and S (1.69%), wherein the sulfur element mainly exists in the form of sulfate. The main chemical components in the roasted agglomerates obtained after the heat treatment in step 3) are TFe (59.30%), SiO2 (7.74%), Al2O3 (2.75%), CaO (0.49%), MgO (0.31%), and S (0.017%), which can be used for iron ore agglomeration / blast furnace ironmaking raw materials. The average concentration of sulfur dioxide in the flue gas of the first 1 / 8 section of the roasting treatment interval along the direction of the trolley is 1.66%, and sulfuric acid can be prepared by wet acid production process.
[0047] Example 4
[0048] 1) The sulfuric acid slag with a moisture content of 16.71% is dried by a rotary dryer, crushed by a damp mill and classified by an air flow classifier to obtain a briquetting raw material with a moisture content of 8.1% and a particle size of 100 μm or less accounting for 100%.
[0049] 2) The briquetting raw material is pressed and formed by a high-pressure briquetting machine under the condition of an online pressing ratio of 2.5 t / cm, to obtain a briquetting block with an ellipsoidal shape, an equivalent volume diameter of 14.4 mm, and a compressive strength of more than 15N;
[0050] 3) The pressed agglomerates are distributed on the belt roasting machine trolley to form a 420 mm distribution layer, and then subjected to blower drying (temperature 300°C, time 3 min, wind speed 1.5 m / s), exhaust drying (temperature 310°C, time 5.5 min, wind speed 1.5 m / s), roasting (temperature 1200°C, time 30 min, wind speed 2.2 m / s), heat soaking (temperature 1050°C, time 3 min, wind speed 1.8 m / s), cooling (time 17 min, wind speed 1.8 m / s), and subsequently sulfur dioxide flue gas and roasted agglomerates are obtained. The sulfur dioxide flue gas is used for the preparation of sulfuric acid after purification, and the roasted agglomerates are used for iron ore agglomeration / ironmaking raw materials for sale.
[0051] In this embodiment, the main chemical components in the sulfate slag (dry basis) are TFe (50.29%), SiO2 (10.13%), Al2O3 (6.80%), CaO (1.57%), MgO (1.87%), and S (1.63%), wherein the sulfur element mainly exists in the form of sulfate. The main chemical components in the roasted agglomerates obtained after the heat treatment in step 3) are TFe (53.73%), SiO2 (10.82%), Al2O3 (7.26%), CaO (1.67%), MgO (2.00%), and S (0.026%), which can be used for iron ore agglomeration / blast furnace ironmaking raw materials. The average concentration of sulfur dioxide in the flue gas of the first 3 / 16 sections of the roasting treatment interval along the direction of the trolley is 1.05%, and sulfuric acid can be prepared by wet acid production process.
[0052] Comparative Example 1
[0053] 1) The high-pressure acid leaching residue of laterite nickel ore with a moisture content of 36.87% was dried by a rotary dryer, crushed by a double-roll crusher and sieved with a high-frequency sieve to obtain an undersize raw material with a moisture content of 10.5% and a particle size of 90% below 100 μm.
[0054] 2) The raw materials under the sieve are pelletized by a disc pelletizer to obtain green balls with a particle size of 14 mm and a moisture content of 25.74%;
[0055] 3) The green balls are heat treated by the iron ore pellet "chain-return-loop" process, wherein the blast drying temperature is 270°C and the time is 8 minutes; the exhaust drying temperature is 280°C and the time is 13 minutes; the preheating temperature is 850°C and the time is 10 minutes; the roasting temperature is 1250°C and the time is 40 minutes; and the cooling time is 32 minutes to obtain sulfur dioxide fume and roasted balls.
[0056] In this comparative example, the main chemical components in the high-pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (27.99%), SiO2 (9.81%), Al2O3 (6.71%), CaO (9.99%), MgO (2.24%), and S (7.60%), wherein the sulfur element mainly exists in the form of sulfate. The main chemical components of the roasted balls obtained after heat treatment in step 3) are TFe (39.10%), SiO2 (13.76%), Al2O3 (9.07%), CaO (13.53%), MgO (3.41%), and S (0.12%), and the roasting flue gas concentration is 0.13%, which cannot be used economically and effectively.
[0057] Comparative Example 2
[0058] 1) The high-pressure acid leaching residue of laterite nickel ore with a moisture content of 36.87% was dried by a rotary dryer to obtain a briquetting raw material with a moisture content of 11.2% and a particle size of 80% below 1 mm.
[0059] 2) The briquetting raw material is pressed and formed by a high-pressure briquetting machine under the condition of an online pressing ratio of 1.5 t / cm, to obtain a briquetting block with an ellipsoidal shape, an equivalent volume diameter of 11.5 mm, and a compressive strength of more than 13N;
[0060] 3) The pressed mass is spread on the belt roasting machine trolley to form a 300 mm material layer, and then subjected to blower drying (temperature 320°C, time 2.5 min, wind speed 1.5 m / s), exhaust drying (temperature 335°C, time 4.5 min, wind speed 1.5 m / s), preheating (temperature 800°C, time 12 min, wind speed 2.2 m / s), roasting (temperature 1230°C, time 40 min, wind speed 2.2 m / s), uniform heat treatment (temperature 1050°C, time 3 min, wind speed 1.8 m / s), cooling (time 17 min, wind speed 1.8 m / s), and sulfur dioxide flue gas and roasted mass are obtained.
[0061] In this comparative example, the main chemical components in the high-pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (27.99%), SiO2 (9.81%), Al2O3 (6.71%), CaO (9.99%), MgO (2.24%), and S (7.60%), of which sulfur is mainly present in the form of sulfate. The main chemical components in the roasted agglomerates obtained after heat treatment in step 3) are TFe (38.96%), SiO2 (13.68%), Al2O3 (9.02%), CaO (13.54%), MgO (3.31%), and S (0.36%), and the sulfur content is greater than 0.2%, which is not conducive to the use of iron ore agglomeration / ironmaking process. The average concentration of sulfur dioxide in the flue gas of the preheating section is 0.21%, and the average concentration of sulfur dioxide in the flue gas of the first 1 / 4 section of the roasting treatment section along the direction of the trolley is 0.75%, which cannot be used economically and effectively. On the one hand, in the absence of a crushing process, the high-decomposition temperature main sulfur-containing phase with good crystallization and coarse particle size in the high-pressure acid leaching residue of laterite nickel ore cannot be refined and activated, and its decomposition reaction rate is slow and the removal time is long. On the other hand, in the gradual heating roasting mode with a preheating process, the low-decomposition temperature sulfur-containing phase is removed first, and the high-decomposition temperature sulfur-containing phase is gradually removed during the heating process, and the concentrated sulfur removal effect is poor. Under the combined influence of these two aspects, the sulfur dioxide concentration in the flue gas is low, which is difficult to recycle economically.
[0062] Comparative Example 3
[0063] 1) The atmospheric pressure acid leaching residue of laterite nickel ore with a moisture content of 28.23% was dried by a rotary dryer, crushed by a double-roll crusher and sieved with a high-frequency sieve to obtain an under-screen briquetting raw material with a moisture content of 11.2% and a particle size of 100 μm or less accounting for 100%.
[0064] 2) The raw materials under the screen are pelletized using a disc pelletizer. The mother balls are very likely to stick to the disc and merge and agglomerate with each other, and cannot form regular spheres;
[0065] In this comparative example, the main chemical components in the atmospheric pressure acid leaching residue of laterite nickel ore (dry basis) are TFe (54.25%), SiO2 (7.07%), Al2O3 (2.51%), CaO (0.45%), MgO (0.28%), and S (1.69%), wherein sulfur element mainly exists in the form of sulfate. After the balling treatment in step 2), it is found that the slag cannot be balled.
[0066] Comparative Example 4
[0067] 1) After drying the sulfuric acid slag with a moisture content of 15.71% with a rotary dryer, crushing it with a double-roll crusher and sieving it with a high-frequency screen, a pellet raw material with a moisture content of 8.1% and a particle size of 100 um or less is obtained.
[0068] 2) The pelletizing raw materials are pelletized by a disc pelletizer to obtain green balls with a particle size of 14 mm and a moisture content of 16.75%;
[0069] 3) The green balls are heat treated by the iron ore pellet "chain-return-loop" process, wherein the blast drying temperature is 255°C and the time is 6 minutes; the exhaust drying temperature is 270°C and the time is 10 minutes; the preheating temperature is 850°C and the time is 10 minutes; the roasting temperature is 1200°C and the time is 30 minutes, and the cooling time is 32 minutes, to obtain sulfur dioxide fume and roasted balls.
[0070] In this embodiment, the main chemical components in the sulfate slag (dry basis) are TFe (50.29%), SiO2 (10.13%), Al2O3 (6.80%), CaO (1.57%), MgO (1.87%), and S (1.63%), wherein the sulfur element is mainly present in the form of sulfate. The main chemical components in the calcined agglomerates obtained after the heat treatment in step 3) are TFe (53.65%), SiO2 (10.81%), Al2O3 (7.25%), CaO (1.66%), MgO (1.99%), and S (0.08%), and the concentration of the calcined flue gas is 0.05%, which cannot be used economically and effectively.
Claims
1. A method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag, characterized in that: The following steps are involved: 1) drying, crushing, grading and briquetting the sulfur-containing iron slag to obtain briquettes; 2) placing the agglomerates on a belt roasting machine trolley, and sequentially performing forced air drying, exhaust air drying, roasting, soaking and cooling to obtain roasted agglomerates; wherein, the flue gas with a sulfur dioxide volume concentration greater than 1.0% generated during the roasting process is separately collected for preparing sulfuric acid, and the roasted agglomerates are used as raw materials for iron ore agglomeration or ironmaking.
2. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: The sulfur-containing iron slag includes at least one of laterite nickel ore high pressure acid leaching slag, laterite nickel ore normal pressure acid leaching slag, laterite nickel ore high pressure-normal pressure combined acid leaching slag, and sulfuric acid slag.
3. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: The sulfur-containing iron slag contains the following main chemical components and mass contents: TFe 25-68%, SiO2 <40%, Al2O3 <18%, CaO <20%, MgO <18%, and S 0.7-12%.
4. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: After drying, crushing and grading, the sulfur-containing iron slag has a moisture content of 2% to 15%, and the mass proportion of particles with a particle size of less than 100 μm is greater than 80%.
5. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: The linear pressure ratio of the briquetting machine during the briquetting process is 1 to 15 t / cm; The equivalent volume diameter of the agglomerate is 5 to 23 mm.
6. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1 or 5, characterized in that: The shape of the mass includes at least one of a cube, a cuboid, a cylinder, a sphere, an ellipsoid and an irregular body.
7. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1 or 5, characterized in that: The thickness of the agglomerates on the belt roasting machine trolley is 50 to 450 mm.
8. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: The blast drying temperature is 150-450°C, the time is 2-6 minutes, and the wind speed is 1.3-1.7 m / s; The temperature of the exhaust drying is 200-500°C, the time is 3-8 minutes, and the wind speed is 1.3-1.7 m / s; The calcination temperature is 1000-1300°C, the time is 20-120 min, and the wind speed is 1.8-2.6 m / s; The temperature of the uniform heating is 800-1200°C, the time is 2-6 minutes, and the wind speed is 1.4-2.2 m / s; the cooling is blast cooling, the time is 15-35 minutes, the wind speed is 1.4-2.2 m / s, and the temperature of the cooling roasted ball material is less than 150°C.
9. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: The calcined agglomerates have a sulfur content of <0.2%.
10. The method for comprehensive recovery of iron and sulfur from sulfur-containing iron slag according to claim 1, characterized in that: During the roasting process, the flue gas in the first 1 / 25 to 3 / 5 length interval of the roasting interval is separately collected for preparing sulfuric acid.